THE INFLUENCE OF CELEBRITY ENDORSERS, PRODUCT QUALITY, AND BRAND IMAGE ON PURCHASE INTENTION ON MS GLOW PRODUCTS IN MALANG CITY - Salsabila, Rona; Rahayu, Yayuk Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to determine the effect of celebrity endorsers, product quality and brand image on consumer buying interest in MS Glow products in Malang City. In this study, using quantitative descriptive research types and approaches. This research was conducted on MS Glow consumers in Malang City. The sample used was 180 respondents. Data analysis using descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that celebrity endorsers had a partial effect on buying interest in MS Glow products in Malang city. product quality has a partial effect on buying interest in MS Glow products in Malang City. brand image has a partial effect on buying interest in MS Glow products in Malang City. Then celebrity endorsers, product quality, and brand image simultaneously affect the purchase intention of MS Glow products in Malang.